Development and Characterization of a Nanoemulgel Containing Cannabidiol and Centella Asiatica for the Topical Treatment of Psoriasis - L. Narwade, Vaibhav; Thakare, Mahesh; Parekh, Pranav; Pavale, Mamta; Londhe, Minakshi; Chivte, Vaishnavi; Ingawale, Chaitali; Galam, Rohit (Journal of Neonatal Surgery, 2025)
Psoriasis is a chronic autoimmune disorder affecting the skin, characterized by excessive keratinocyte proliferation, inflammation, and the formation of erythematous plaques. Despite the availability of numerous treatments—ranging from corticosteroids to biologics—most suffer from limited efficacy, poor patient compliance, and adverse effects. To address these limitations, a novel nanoemulgel incorporating Cannabidiol (CBD) and Centella asiatica was developed and evaluated. CBD offers potent anti-inflammatory and antioxidant activity, while Centella asiatica contributes wound healing and regenerative properties. Nanoemulgels were formulated using high-energy ultrasonication and incorporated into a gel matrix with Carbopol 940. The resulting formulation was evaluated for physicochemical properties, drug content, stability, in vitro drug release, and skin permeation. The CBD-CA nanoemulgel showed excellent uniformity, sustained release, improved skin penetration, and ideal rheological properties, indicating its potential as an effective, patient-friendly therapy for the topical treatment of psoriasis.